(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Bleeding disorders are a group of conditions in which there is a problem with the body’s blood clotting process. These disorders can lead to heavy and prolonged bleeding after an injury or surgery. Bleeding can also begin on its own and may be difficult to stop. Bleeding disorders can be either inherited or acquired. Acquired bleeding disorders are more common than inherited bleeding disorders.1 Periodontal disease is defined as an inflammatory condition of supporting tissue of teeth cause by specific microorganisms or group of specific microorganisms resulting in progressive destruction of periodontal ligament and alveolar bone with periodontal pocket formation, gingival recession or both.2 Bleeding disorder may also increase the severity of the periodontal disease and due to the risk of uncontrolled haemorrhagic episodes, make the periodontal treatment challenging. The aim of this review is to compile the current knowledge of bleeding abnormalities and elaborate preoperative and intraoperative measures in the management of periodontal treatment in patients with bleeding disorder.